2021
DOI: 10.14802/jmd.20098
|View full text |Cite
|
Sign up to set email alerts
|

Chorea as a Presentation of SARS-CoV-2 Encephalitis: A Clinical Case Report

Abstract: Central nervous system (CNS) involvement in SARS-CoV-2 is now a known fact, likely due to viral transmission through the olfactory nerve and high brainstem viral load, which also suggests dissemination in the ambiguus and solitary nuclei from the respiratory tract via the vagus nerve. 1 Anosmia and ageusia findings are justified by a potential large cohort study. It may only be an interesting coincidence that hyposmia disorders are normal in premature Parkinson's disease (usually only in the prodromal phase) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The first video of the patient showed abnormal movements that were involuntary, abrupt, nonstereotyped, irregular, sometimes large-amplitude, and unpredictable on the right leg and arm, defined as chorea by the authors. 2 However, as pointed out in the letter, 3 myoclonus was also observed in the first video, and all abnormal movements in the other videos appear to be myoclonus. 2 Therefore, the patient may have a combination of abnormal movements due to both myoclonus and chorea.…”
Section: Dear Editormentioning
confidence: 65%
See 1 more Smart Citation
“…The first video of the patient showed abnormal movements that were involuntary, abrupt, nonstereotyped, irregular, sometimes large-amplitude, and unpredictable on the right leg and arm, defined as chorea by the authors. 2 However, as pointed out in the letter, 3 myoclonus was also observed in the first video, and all abnormal movements in the other videos appear to be myoclonus. 2 Therefore, the patient may have a combination of abnormal movements due to both myoclonus and chorea.…”
Section: Dear Editormentioning
confidence: 65%
“…2 However, as pointed out in the letter, 3 myoclonus was also observed in the first video, and all abnormal movements in the other videos appear to be myoclonus. 2 Therefore, the patient may have a combination of abnormal movements due to both myoclonus and chorea.…”
Section: Dear Editormentioning
confidence: 65%
“…We reviewed the relevant literature published up to April 2021 and extracted three reports of acute chorea with mild signs of encephalopathy and evidence of concurrent Covid‐19 (see Table 1). 4–6 All the patients had mild‐to‐moderate leukocytosis and absence of oligoclonal bands in the CSF. Our case, the only one with CSF follow‐up, suggests that the immune response, in the absence of an effective immunomodulating therapy, can persist for a long time after resolution of the triggering event.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study by Ray et al [8] on the prevalence of COVID-19 neurological manifestations among 1,334 children, two cases of acute chorea were reported. Byrnes et al [9], Hassan et al [5] and Cotta Ramusino et al [10] reported COVID-19-associated chorea in adults, most probably due to non-infectious encephalitis. Ghosh et al [11] reported a case of chorea in the course of diabetic ketoacidosis triggered by SARS-CoV-2 infection.…”
mentioning
confidence: 99%